A Nodular Lesion of the Foot Detected by 18F-FDG PET/CT in Mycosis Fungoides: A Plantar Wart. (March 2019) - Fujita, Yasuyuki; Natsuga, Ken; Manabe, Osamu; Hirata, Kenji; Shimizu, Hiroshi
Abstract : Abstract: A 34-year-old Japanese woman presented with widespread scaly erythema that had enlarged over 2 years. A skin biopsy revealed the diagnosis of mycosis fungoides (patch stage, T1b N0 M0 B0), a most frequent cutaneous T-cell lymphoma. 18 F-FDG PET/CT scan unexpectedly showed intense uptake on the left sole, which suggested a tumorous mycosis fungoides lesion (SUVmax = 6.2). Careful examination revealed the mass to be a typical plantar wart of 2 cm in diameter that the patient had not recognized. With repeated cryotherapy, the wart disappeared in 6 months, and follow-up 18 F-FDG PET/CT showed no abnormal uptake on the left sole.